PENGARUH LATIHAN BEBAN TERHADAP KECEPATAN LEMPARANPITCHING BALL PADA ATLET SOFTBALL ACEHTAHUN 2015 - Awaluddin Awaludin.; Nurmasyitah Nurmasyitah. (Jurnal Pesona Dasar, 2018)
The study is titled "The Effect of Weight Training on Speed Pitching Ball At Athlete SoftballAceh Year 2015". This study aims to determine the Effect of Load Training on Speed Pitching Ball At Athlete Soatball Aceh Year 2015. Samples in this study are athletes Softball Aceh special pitcher which amounted to 8 people. The sampling technique is done by totalsampling, ie the sample is taken entirely. Data collection techniques used in this study are as follows: (1) pitching ball throwing test is done by doing Pitching test. Data is processed by using statistical formula in the form of calculation of mean value, standard deviation, and test of two mean (ttes). The result of this research is that there is Influence of Load Exercise on Speed of Pitching Ball at AtletSoftballAceh Year 2015 with average of 9,2357, with t-test of 0,357 and t-table equal to 0,131, so it is clear that t-test is bigger rather than t-tables, it can be concluded that weight training (X) on increasing the speed of the pitching ball (Y) is significant. Hence the hypothesis stating that there is Effect of Load Training on Speed Pitching ball pitch at Athlete Softball Aceh Year 2015 acceptable truth. Suggestion from this research is if exercise done in accordance with its understanding and concept there will be improvement of physical quality, technique and mental in athlete.